Numerical Simulation Study on Compression Characteristics of Gravelly Soil Mixture Based on Soft Servo Method. (10th July 2021) - Ning, Yu; Huang, Qingfu; Shi, Chong; Meng, Qingxiang
Abstract : Because of complex mechanical properties and deformation mechanism, gravel soil mixture is an important medium of concern in the field of geotechnical engineering. Based on the continuous-discontinuous coupling algorithm formed by the structure shell elements and the particle discrete element method (PFC3D), the soft servo loading of the sample is realized, and the typical triaxial compression test data are used to calibrate mesoscale parameters. Furthermore, the numerical tests under different rock contents and confining pressure are carried out. The change rule of shear strength of mixed medium is discussed. It shows that the continuous-discontinuous coupling algorithm achieves a good effect in reflecting the deformation process. Under the mechanism of the flexible servo, the failure mode of the sample takes on drum-failure mode, and the internal of the damaged sample forms an obvious asymmetric X-shaped shear band. With the increase of stone content, the internal friction angle and cohesive force distribution of the sample have certain discreteness, but on the whole, the internal friction angle and cohesive force increase with the increase of stone content. The results can provide a reference for the parameter determination of mixed mediums such as gravel soil.